Pentingnya Manajemen Strategik dalam Meningkatkan Kualitas Pendidikan - Nurasha Alfahira; Desi Fitri Yani; Dessy Masliani; Ahmad Rinaldi Siregar; Hasbih Sholeh Suryadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to describe or explain the literature review regarding the importance of strategic management in improving the quality of education. This research method uses a qualitative research method using an observation, interview, documentation and literature study approach or based on literature review through book reviews and journals. The research steps start from collecting articles, reducing artcles, discussing and concluding. The research results show that the importance of strategic management in improving the quality of education can have a positive influence on the educational institution itself. Improving the quality of education will of course have an impact on graduates from these schools. Through strategic management, future opportunities can be expanded and realized risks can be minimized. Strategic management can only be achieved if all parties have a direct interest in the school such as school administrators, parents, teachers and staff involved.